Reconstructing molar growth from enamel histology in extant and extinct Equus. Issue 1 (December 2017) - Nacarino-Meneses, Carmen; Jordana, Xavier; Orlandi-Oliveras, Guillem; Köhler, Meike
Abstract The way teeth grow is recorded in dental enamel as incremental marks. Detailed analysis of tooth growth is known to provide valuable insights into the growth and the pace of life of vertebrates. Here, we study the growth pattern of the first lower molar in several extant and extinct species ofEquus and explore its relationship with life history events. Our histological analysis shows that enamel extends beyond the molar's cervix in these mammals. We identified three different crown developmental stages (CDS) in the first lower molars of equids characterised by different growth rates and likely to be related to structural and ontogenetic modifications of the tooth. Enamel extension rate, which ranges from ≈400 μm/d at the beginning of crown development to rates of ≈30 μm/d near the root, and daily secretion rate (≈17 μm/d) have been shown to be very conservative within the genus. From our results, we also inferred data of molar wear rate for these equids that suggest higher wear rates at early ontogenetic stages (13 mm/y) than commonly assumed. The results obtained here provide a basis for future studies of equid dentition in different scientific areas, involving isotope, demographic and dietary studies.